Las aventuras de Huckleberry Finn - Twain, Mark, 1835-1910 (Akal bolsillo, 2011)
Desperate to escape his abusive father and the constraints of the civilized life, young Huck Finn fakes his death and, with the help of his slave friend Jim, embarks on a vagabond life rafting down the Mississippi River. Yet life is anything but carefree for Huck and Jim. Their travels bring them into contact with scores of rogues, rascals, ruffians, hucksters, and law-abiding citizens who would as soon seen Jim returned to his owners and Huck to his Pa. Looking out for each other, Huck and Jim forge a bond that protects them from the prejudices and bigotry of their time and place, and a society whose rules and regulations seem as perplexing as they are inflexible.